KUALITAS PERAIRAN PANTAI SERIBU RANTING JEPARA - Setiyowati, Desti; Mustofa, Arif (Jurnal Disprotek, 2024)
WATER QUALITY OF JEPARA'S SERIBU RANTING BEACHSeribu Ranting Beach is located between two river estuaries. These two river estuaries are a source of sediment that enters coastal waters. These sediments can cause shallowing of coastal waters, which can disrupt the marine ecosystem, so Seribu Ranting Beach has a high potential for pollution. This research aims to determine the condition of water quality at Seribu Ranting Beach. This research was carried out in October 2023 in the waters of Seribu Ranting Beach. The research method used is descriptive exploratory. The data collection point is divided into 3 stations. Water quality data was collected, namely pH, temperature, salinity and dissolved oxygen using multimeter parameters, turbidity using a turbidity meter, depth and brightness using a Secchi disk, and current speed using a probe ball. The results of this research are physical parameters consisting of water temperature ranging from 31.3 - 35.8 °C, current speed ranging from 0.03 - 0.04 m/s, depth ranging from 0.6 - 0.7 m, brightness ranging from between 0.15 – 0.30 m and turbidity ranging from 35 – 55 NTU. Chemical parameters consist of pH ranging from 6.98 – 7.77, salinity ranging from 25 – 30 ‰ and DO ranging from 5.7 – 9.3 mg/L. The water quality of Seribu Ranting Beach meets marine water quality standards and is classified as adequate conditions for the survival of organisms or marine biota based on Government Regulation of the Republic of Indonesia Number 22 of 2021, namely the parameters of temperature, pH, salinity and dissolved oxygen. Meanwhile, depth, brightness and turbidity do not meet the quality standards for marine aquatic organisms.Pantai Seribu Ranting terletak di antara dua muara sungai. Kedua muara sungai ini menjadi sumber sedimen yang masuk ke perairan pantai. Sedimen-sedimen tersebut dapat menyebabkan pendangkalan perairan pantai, yang dapat mengganggu ekosistem laut, sehingga Pantai Seribu Ranting memiliki potensi pencemaran yang tinggi. Penelitian ini bertujuan untuk mengetahui kondisi kualitas perairan di Pantai Seribu Ranting. Penelitian ini dilaksanakan pada bulan Oktober 2023 di wilayah perairan Pantai Seribu Ranting. Metode penelitian yang digunakan yaitu deskriptif eksploratif. Titik pengambilan data dibagi menjadi 3 stasiun. Pengambilan data kualitas air yaitu pH, suhu, salinitas dan oksigen terlarut menggunakan multicheker parameter, kekeruhan menggunakan turbidity meter, kedalaman dan kecerahan menggunakan secchi disk, dan kecepatan arus menggunakan bola duga. Hasil dari penelitian ini yaitu parameter fisika terdiri suhu air berkisar antara 31,3 – 35,8 °C, kecepatan arus berkisar 0,03 – 0,04 m/s, kedalaman berkisar antara 0,6 – 0,7 m, kecerahan berkisar antara 0,15 – 0,30 m dan kekeruhan berkisar antara 35 – 55 NTU.  Parameter kimia terdiri dari pH berkisar antara 6,98 – 7,77, salinitas berkisar antara 25 – 30 ‰ dan DO berkisar 5,7 – 9,3 mg/L. Kualitas perairan Pantai Seribu Ranting yang memenuhi standar baku mutu perairan laut dan tergolong pada kondisi yang tercukupi untuk kelangsungan hidup organisme atau biota perairan laut berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 22 Tahun 2021 adalah pada parameter suhu, pH, salinitas, dan oksigen terlarut. Sedangkan kedalaman, kecerahan dan kekeruhan tidak memenuhi standar baku mutu biota perairan laut.